Problems of regional economic development: an international conference in Tuva - Oorzhak, Valeriy O.; Balakina, Galina F. (The New Research of Tuva, 2020)
The article presents an overview of the 3rd International Scientific and Practical Conference "Regional Economy: Technologies, Economics, Ecology and Infrastructure," which took place from October 23 to 25, 2019 at the Tuvinian Institute of Complex Development of Natural Resources at the Russian Academy of Sciences (Kyzyl, Russia). The conference was dedicated to the 25th anniversary of the institute and the 45th anniversary of the first institution of academic research in Tuva. The main purpose of the conference was to study and analyze the state of economy of the Republic of Tuva, in the regions of Siberia and neighbouring territories. Through discussions and analysis of the outcomes of research into economic, technological and environmental processes in the Republic of Tuva and neighboring regions, proposals were made on how to ensure dynamic and sustainable development of these territories under current conditions. The papers accepted for the conference were presented at the plenary session and five panels. Some paper suggestions were also discussed, including those concerning other regions of Russia and the world. The conference concluded by reflecting on its outcomes and formulating policy recommendations for the authorities of Tuva.